PD-L1 and PD-L2 are differentially regulated by Th1 and Th2 cells - Loke, P'ng (The National Academy of Sciences, 2003)
PD-L1 and PD-L2 are ligands for PD-1, a costimulatory molecule that plays an inhibitory role in regulating T cell activation in the periphery. We find that PD-L1 is highly expressed on inflammatory macrophages as compared with resident peritoneal macrophages but can be induced on resident macrophages by classical activation stimuli such as lipopolysaccharide, IFN-γ, and polyinosinic-polycytidylic acid. Further up-regulation of PD-L1 on inflammatory macrophages can also be induced by subsequent exposure to lipopolysaccharide and IFN-γ. In contrast, PD-L2 is not expressed on inflammatory macrophages but can be induced by alternative activation via IL-4. Although PD-L1 is highly inducible on a variety of antigen-presenting cell lines as well as resident macrophages, PD-L2 is most significantly inducible only on inflammatory macrophages. PD-L1 up-regulation depends on TLR4 and STAT1, whereas PD-L2 expression depends on IL-4Rα and STAT6. Consistent with these results, T helper 1/T helper 2 (Th1/Th2) cells also differentially up-regulate PD-L1 and PD-L2 expression on inflammatory macrophages. Hence, Th1 cells as well as microbial products can enhance PD-L1 expression on many different macrophage populations, whereas Th2 cells instruct only inflammatory macrophages to up-regulate PD-L2. These results suggest that PD-L1 and PD-L2 might have different functions in regulating type 1 and type 2 responses.